Genetic differences between type 1 diabetes with and without other autoimmune diseases. Issue 7 (8th June 2018) - Shimura, Kanako; Miura, Junnosuke; Kawamoto, Manabu; Kawaguchi, Yasushi; Yamanaka, Hisashi; Uchigata, Yasuko
Abstract: Background: Clusters of autoimmune diseases (ADs) are present in some people with type 1 diabetes. This clustering suggests the existence of common genetic backgrounds for abnormal autoimmunity in these individuals. However, the genetic differences between type 1 diabetes patients with and without other ADs are not well known. Methods: To investigate the clinical background and genetic differences between type 1 diabetes patients with and without other ADs, single nucleotide polymorphisms (SNPs) in the CTLA4, SUMO4, PTPN22, IRF5, STAT4, and BLK genes were analysed by using either a TaqMan assay or direct sequencing. The frequencies of alleles, genotypes of each gene, and the human leukocyte antigen (HLA) haplotype were analysed to investigate differences among 3 groups: type 1 diabetes with systemic ADs (group A), type 1 diabetes with other organ‐specific ADs (group B), and type 1 diabetes without other ADs (group C). Results: The frequency of the C allele in the ‐1123G > C SNP in the PTPN22 gene promoter was significantly higher in groups A and B than in group C ( P = .0258 and .0207, respectively). The allele frequencies of the other SNPs were comparable. The frequency of HLA DRB1*0405‐DQB1*0401 was significantly higher in groups A and B than in group C ( P = .021 and .0395, respectively). Conclusions: The ‐1123G > C SNP in the PTPN22 gene promoter and HLA DRB1*0405‐DQB1*0401 might influence the concurrence of systemic and organ‐specific ADs in patients with type 1 diabetes.